Critical factors in employee training for the automotive industry: A systematic review of performance-driven training strategies - Saleh, Hasan; Mohd Faridzul Basri, Shuaibah Ainiah (Human Resource Management Academic Research Society, 2024)
This systematic literature analysis explores the fundamental role of training and development (T&D) in enhancing employee performance within the automotive industry’s R&D departments. Given the industry's changing market needs and quickening pace of technical change, T&D programs are crucial in ensuring that employees achieve the required performance. Key topics in the evaluation include employee engagement, skill development, technology integration, and thorough organisational and requirement studies to determine the effects of structured T&D programs on workforce performance. Important factors including training quality, a variety of approaches, assessment procedures, budgetary allocation, and scheduling were examined to ascertain how they affect the efficacy of T&D initiatives. This study also investigates how Social Learning Theory serves as a basis for productive employee cooperation and information sharing. Furthermore, as innovation is essential in gaining competitive edge in R&D-intensive industries, the study emphasises how important it is to match training curricula with technology developments. Ultimately, this review offers leaders in the automotive sector insightful information, indicating that wellcrafted T&D frameworks not only enhance individual performance and flexibility, but also promote a culture of ongoing learning, innovation, and long-term organisational success in a changing market.